Elastography Techniques for the Assessment of Liver Fibrosis in Non-Alcoholic Fatty Liver Disease - Yasushi Honda (International Journal of Molecular Sciences, 2020)
Non-alcoholic fatty liver disease (NAFLD) is expected to increase in prevalence because of the ongoing epidemics of obesity and diabetes, and it has become a major cause of chronic liver disease worldwide. Liver fibrosis is associated with long-term outcomes in patients with NAFLD. Liver biopsy is recommended as the gold standard method for the staging of liver fibrosis. However, it has several problems. Therefore, simple and noninvasive methods for the diagnosis and staging of liver fibrosis are urgently needed in place of biopsy. This review discusses recent studies of elastography techniques (vibration-controlled transient elastography, point shear wave elastography, two-dimensional shear wave elastography, and magnetic resonance elastography) that can be used for the assessment of liver fibrosis in patients with NAFLD.